Effects of visual stimulation on cortico-spinal coherence during isometric hand contraction in humans - Safri, Norlaili Mat (Elsevier BV, 2006)
The effects of visual stimuli on cortico-spinal synchronization were investigated by measuring the coherence between electroencephalogram (EEG) and electromyogram (EMG) during isometric contraction of the first dorsal interosseous muscle of the right hand. Because a spinal motoneuron and the corresponding muscle fibers form a motor unit with one-to-one correspondence of their action potentials, the EMG indirectly measures the activity of the corresponding spinal neuronal group. The tasks were isometric contraction (Control condition); and isometric contraction with concurrent ignoring of visual stimuli (VS condition). By comparing the Control and VS conditions, the following results were obtained. The coherence increased significantly in magnitude, but was unchanged in frequency range (beta band) and scalp location; the EEG and EMG spectral power in the beta band were unchanged in amplitude; and the alpha and gamma bands of EEG spectral power were significantly increased and decreased, respectively. These findings suggest that the cortico-muscular coherence reflects the cognitive effort needed to maintain isometric muscle contraction. When visual stimuli need to be ignored, the cognitive effort and cortico-spinal coherence are enhanced.